Acral cutaneous malignant melanoma treated with linear accelerator-based boron neutron capture therapy system: a case report of first patient - Igaki, Hiroshi; Nakamura, Satoshi; Yamazaki, Naoya; Kaneda, Tomoya; Takemori, Mihiro; Kashihara, Tairo; Murakami, Naoya; Namikawa, Kenjiro; Nakaichi, Tetsu; Okamoto, Hiroyuki; Iijima, Kotaro; Chiba, Takahito; et al. (Frontiers in Oncology, 2023)
This study reports the first patient treatment for cutaneous malignant melanoma using a linear accelerator-based boron neutron capture therapy (BNCT) system. A single-center open-label phase I clinical trial had been conducted using the system since November 2019. A patient with a localized node-negative acral malignant melanoma and the largest diameter of the tumor ≤ 15 cm who refused primary surgery and chemotherapy was enrolled. After administering boronophenylalanine (BPA), a single treatment of BNCT with the maximum dose of 18 Gy-Eq delivered to the skin was performed. The safety and efficacy of the accelerator-based BNCT system for treating localized cutaneous malignant melanoma were evaluated. The first patient with cutaneous malignant melanoma in situ on the second finger of the left hand did not develop doselimiting toxicity in the clinical trial. After BNCT, the treatment efficacy was gradually observed, and the patient achieved PR within 6 months and CR within 12 months.Moreover, during the follow-up period of 12 months after BNCT, the patient did not exhibit a recurrence without any treatment-related grade 2 or higher adverse events.Although grade 1 adverse events of dermatitis, dry skin, skin hyperpigmentation, edema, nausea, and aching pain were noted in the patient, those adverse events were relieved without any treatment. This case report shows that the accelerator-based BNCT It was suggested that BNCT wouldmay become a promising treatment modality for cutaneous malignant melanoma. We expect further clinical trials to reveal the efficacy and safety of the accelerator-based BNCT for cutaneous malignant melanoma.